Studi Eksegesis Amsal 1-9: Suatu Antitesis Antara Orang Bebal dan Orang Bijak - Riski Riski; Farel Yosua Sualang; Endah Totok Budiyono (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2023)
The purpose of this research is to understand the meaning of fear of God in the text of Proverbs 1-9. Because the phrase